2016
DOI: 10.2147/ndt.s107777
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of binge eating disorder in relation to diagnostic criteria

Abstract: The objective of this review was to examine the evidentiary basis for binge eating disorder (BED) with reference to the Diagnostic and Statistical Manual of Mental Disorders – Fifth Edition (DSM-5) diagnostic criteria for BED. A PubMed search restricted to titles and abstracts of English-language reviews, meta-analyses, clinical trials, randomized controlled trials, journal articles, and letters using human participants was conducted on August 7, 2015, using keywords that included “binge eating disorder,” DSM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 90 publications
(296 reference statements)
1
35
0
2
Order By: Relevance
“…In summary, these findings, derived from a large nationally representative sample of U.S. adults, suggest that the presence of overvaluation in BED signals greater severity (i.e., in this case, greater functional impairment) and therefore warrants consideration as a diagnostic specifier in future editions of the DSM . Research with clinical and community samples has found that overvaluation provides more robust information about severity of BED than the new DSM‐5 severity specifier based on binge‐eating frequency.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In summary, these findings, derived from a large nationally representative sample of U.S. adults, suggest that the presence of overvaluation in BED signals greater severity (i.e., in this case, greater functional impairment) and therefore warrants consideration as a diagnostic specifier in future editions of the DSM . Research with clinical and community samples has found that overvaluation provides more robust information about severity of BED than the new DSM‐5 severity specifier based on binge‐eating frequency.…”
Section: Discussionmentioning
confidence: 86%
“…Grilo argued, however, that overvaluation should not be a required criterion, as it would exclude a significant proportion of persons with BED with clinically meaningful concerns . This position has received continued support .…”
Section: Introductionmentioning
confidence: 99%
“…Binge eating symptoms were first noted in 1959 by psychiatrist Albert Stunkard when describing the abnormal eating pattern of a 30-year-old salesman (6) , but the American Psychiatric Association has only recently recognized BED as a formal category of psychiatric disorder (7) . There is a wide spectrum of clinical manifestations of eating behaviors, from overeating and gluttony to variable binge symptoms until full Diagnostic and Statistical Manual of Mental Disorders 5th edition (DSM-5) BED-criteria are met (8) . Therefore, the diagnosis of BED is challenging, due to its complexity and variability in phenotypic presentation (9) .…”
Section: Introductionmentioning
confidence: 99%
“…An increase in marble burying can predict BE 67,68 and thus, our results suggest that human genetic polymorphisms affecting CYFIP1 expression could modulate OC behavior and risk for eating disorders 41,42 . OC behaviors are associated with both BE 37,38 and PWS hyperphagia 40 . However, in our 1 4 studies, there was no clear relationship between OC-like behaviors and PF intake.…”
Section: Oc-like Behavior and Pf Intake In Cyfip1 +/Micementioning
confidence: 99%